Cli-fi videos can increase charitable donations: experimental evidence from the United Kingdom - Shreedhar, Ganga; Sabherwal, Anandita; Maldonado, Ricardo (Frontiers in Psychology, 2024)
Recent research has begun to investigate if climate fiction, or cli-fi, can increase people’s support for pro-climate initiatives. Emerging evidence focuses on whether cli-fi stories affect people’s self-reported emotions, attitudes, and intentions. Few studies, however, examine the effect of such stories on revealed behavior, and whether the cli-fi story medium, i.e., whether stories are presented in text, audio, or audio-visual format, matters. We investigate the causal effect of cli-fi stories, and the medium through which they are communicated (textual, audio, or audio-visual) on self-reported support for climate policy, individual and collective action intentions, and a revealed measure of charitable donations. In a pre-registered online experiment (n = 1,085 UK adults), participants were randomly assigned to one of 5 conditions – to read scientific information about climate change (scientific information condition), read a story unrelated to the environment (control), read a cli-fi story in which a protagonist took intentional pro-environmental actions (fiction text), listen to the same cli-fi story in audio format (fiction audio), or watch an animation of the cli-fi story (fiction video). When comparing the fiction-text, fact-text, and control conditions, we found that cli-fi stories are not always more effective than alternative climate communications: participants in the fact-text condition reported higher support for climate policies, and intentions of taking individual environmental actions, and negative feelings of sadness, disappointment, and guilt, compared to the text-based control and cli-fi text condition. When comparing the cli-fi media format, we found that cli-fi videos were most effective in increasing pro-environmental charitable donations in an incentivized choice task, and self-reported feelings of happiness, hope, and inspiration. The findings show that scientific information about the climate and climate-fiction have an important place in the climate communications toolkit and can offer distinct pathways to enhance support for policy and behavioral change. Communicators seeking to inspire individual pro-environmental actions can consider telling cli-fi stories in video, which may be more compelling. And communicators seeking to enhance public support for societal changes, via climate policies, may benefit from disseminating scientific information about climate change.